Effect of Yogurt Fermented by Lactobacillus Fermentum TSI and L. Fermentum S2 Derived from a Mongolian Traditional Dairy Product on Rats with High-Fat-Diet-Induced Obesity - Won-Young Cho; Go-Eun Hong; Ha-Jung Lee; Su-Jung Yeon; Hyun-Dong Paik; Yoshinao Z. Hosaka; Chi-Ho Lee (Foods, 2020)
This study aimed to investigate the metabolic effect of yogurt fermented by Lactobacillus fermentum TSI and S2 isolated from a Mongolian traditional dairy product on rats with high-fat-diet-induced obesity. Quality characteristics of yogurt fermented by commercial starter (CON), L. fermentum TSI2 (TSI2 group), L. fermentum S2 (S2 group), and mixed TSI2 and S2 strains at 1:1 (MIX group), were verified. Six-week-old male Sprague-Dawley rats were divided into five groups and administered the following diets: group NOR, normal diet with oral saline administration; group HF, high-fat diet (HD) with oral saline administration; group TSI, HD and L. fermentum TSI-fermented yogurt; group S2, HD and L. fermentum S2-fermented yogurt; and group MIX, HD and MIX-fermented yogurt. After eight weeks, the HD groups displayed significantly increased body weight and fat, serum cholesterol, and abdominal adipose tissue levels. However, serum HDL cholesterol levels were higher, triglyceride levels were lower, and abdominal adipocytes were smaller in the TSI and S2 groups than in the HF group. These results indicate that L. fermentum TSI reduces abdominal fat and improves blood lipid metabolism in HD-induced obese rats.